Cultural-historical meaning of religion and modern kazakhstan society: pointsofcontact (Journal of Philosophy Culture and Political Science, 2018)
The task of undevstanding the contemporary religions situation from the perspective of social and philosophicalcognition is posed. The latter involves the study of universal laws and society features, considered in integritywith the interrelation of its sides – individual, culture and society. The worldview foundations of Kazakhstanisociety is taken into consideration. On the basis of the problem’s and historical analysis do the conclusion thatthe religion, in-fi rst, is an integral part of sociocultural life today. Secondly, being the universal phenomenon ofuniversal culture, it has, at the same time, lines of an originality. And, thirdly, the most optimal answer to calls ofspiritual and religious life is the organic combination of the culturological and sociocultural, all-civilization andregional approaches promoting identifi cation, preservation and consolidation of cultural and historical sense ofreligion in the conditions of globalization.Key words: religion, mythical-religious picture of the world of Turk’s ethnos, religious situation,modern Kazakhstan society.